2013 IEEE International Symposium on Information Theory 2013
DOI: 10.1109/isit.2013.6620426
|View full text |Cite
|
Sign up to set email alerts
|

Capacity and security of heterogeneous distributed storage systems

Abstract: Abstract-We study the capacity of heterogeneous distributed storage systems under repair dynamics. Examples of these systems include peer-to-peer storage clouds, wireless, and Internet caching systems. Nodes in a heterogeneous system can have different storage capacities and different repair bandwidths. We give lower and upper bounds on the system capacity. These bounds depend on either the average resources per node, or on a detailed knowledge of the node characteristics. Moreover, we study the case in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 25 publications
1
50
0
Order By: Relevance
“…Combined with a tree-structured regeneration topology, it is shown that RC can further save the network bandwidth [20], [21]. Some studies [16], [22] focus on the capacity bound for a heterogeneous model. However, all the above studies do not distinguish the costs between intra-rack and cross-rack communications in data centers.…”
Section: Related Workmentioning
confidence: 99%
“…Combined with a tree-structured regeneration topology, it is shown that RC can further save the network bandwidth [20], [21]. Some studies [16], [22] focus on the capacity bound for a heterogeneous model. However, all the above studies do not distinguish the costs between intra-rack and cross-rack communications in data centers.…”
Section: Related Workmentioning
confidence: 99%
“…For a given weighting factor , let ˛ ,ˇ 1 ,ˇ 2 , : : : ,ˇ n be the optimal solution to the minimisation problem stated in (18). Now, we prove that the optimal download amount vectorˇ D ˇ 1 ,ˇ 2 , : : : ,ˇ n must satisfy the constraint in (19).…”
Section: Case B: Homogeneous Storage Amountmentioning
confidence: 89%
“…The authors in [10] presented the secrecy capacity of a network-coded storage system in which an eavesdropper can observe a fixed number of nodes. In [11], the secrecy capacity was obtained for nodes having different storage capacities and different repair bandwidths. A coding scheme that achieves the upper bounds on secrecy capacity was proposed in [13].…”
Section: A Node Eavesdropping Problemmentioning
confidence: 99%